The H-index in Life and Health Sciences: Advantages, Drawbacks and Challenging Opportunities - Dinis-Oliveira, Ricardo J. (Current Drug Research Reviews, 2019)
In recent years, there has been a significant increase in the number of scientific publications. The h-index offers a consistent estimation method about a researcher’s overall scientific achievements since it combines the total number of publications (i.e., productivity) and the number of citations (i.e., quality of those publications). In other words, the h-index is intended to measure simultaneously the quality and quantity of scientific output in a cumulative approach and does not provide data regarding the recent productivity. This editorial presents advantages and limitations of h-index that all researchers in health sciences need to be aware of, especially if this metric is used for professional progression, and discusses the simple modification indexed to “academic/scientific age”. It is obvious that no single metric is perfect, and the use of two or more metrics is more prone to success.
Keywords: limitations